2011
DOI: 10.1007/s00122-011-1761-y
|View full text |Cite
|
Sign up to set email alerts
|

Breeding maize as biogas substrate in Central Europe: I. Quantitative-genetic parameters for testcross performance

Abstract: Biofuels have gained importance recently and the use of maize biomass as substrate in biogas plants for production of methane has increased tremendously in Germany. The objectives of our research were to (1) estimate variance components and heritability for different traits relevant to biogas production in testcrosses (TCs) of maize, (2) study correlations among traits, and (3) discuss strategies to breed maize as a substrate for biogas fermenters. We evaluated 570 TCs of 285 diverse dent maize lines crossed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
4
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 29 publications
6
32
4
4
Order By: Relevance
“…Our finding of a strong influence of DM yield on estimated methane yield (Table 1, Figure 1) was confirmed by Graß et al [7], Grieder et al [19], Mayer et al [27], and Sieling et al [13]. Consequently, we recognized highest estimated methane yield of silage maize in Aiterhofen when cultivated in the rotation (catch crop mustard -) silage maize-winter wheat-winter wheat (9388 Nm 3¨h a´1) and lowest in this rotation in Harste (6458 Nm 3¨h a´1).…”
Section: Estimated Methane Yield Of Silage Maize and Sugar Beet Root supporting
confidence: 89%
See 2 more Smart Citations
“…Our finding of a strong influence of DM yield on estimated methane yield (Table 1, Figure 1) was confirmed by Graß et al [7], Grieder et al [19], Mayer et al [27], and Sieling et al [13]. Consequently, we recognized highest estimated methane yield of silage maize in Aiterhofen when cultivated in the rotation (catch crop mustard -) silage maize-winter wheat-winter wheat (9388 Nm 3¨h a´1) and lowest in this rotation in Harste (6458 Nm 3¨h a´1).…”
Section: Estimated Methane Yield Of Silage Maize and Sugar Beet Root supporting
confidence: 89%
“…The yield level of silage maize in our trials was slightly higher compared to results of Graß et al [7], Grieder et al [19], and Herrmann et al [20], who reported a silage maize DM yield between 19.1 and 21.8 t¨ha´1¨a´1 but not exclusively for highly-productive sites. Our mean DM yield of sugar beet root in crop rotations (Aiterhofen and Harste: 17.0-23.0 t¨ha´1¨a´1) was in the lower range in comparison to results of Starke and Hoffmann [14] who detected DM yield of different varieties between 17 and 27 t¨ha´1¨a´1.…”
Section: Dry Matter Yield Of Silage Maize and Sugar Beet Root Cultivacontrasting
confidence: 78%
See 1 more Smart Citation
“…Therefore, inbred lines are evaluated in crosses with different testers for their testcross performance (TP). In a companion study based on TP, Grieder et al (2011b) examined different traits in a broad germplasm collection and discussed their results with respect to breeding of biogas maize. They observed a preponderance of general combining ability (GCA) over specific combining ability (SCA) effects for agronomic as well as quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of r g between LP and TP depend on the predominant type of gene action (Hallauer and Miranda 1988;Mihaljevic et al 2005;Smith 1986) and, therefore, vary for different traits. For forage maize, correlations between LP and TP for DMY, days to silking (DTS) and various quality traits ranged from moderate to strong (Argillier et al 1995;Gurrath et al 1991;Kreps et al 1998;Seitz et al 1992). Thus, estimates of r g between LP and TP for novel traits like MFY and MY, which are important for biogas maize, are needed to develop optimum breeding strategies.…”
Section: Introductionmentioning
confidence: 99%